Towards a more robust non-rigid robotic joint - Pinto, Vítor H. (2021)
The following paper presents an improved, low cost, non-rigid joint that can be used in both robotic manipulators and leg-based traction robotic systems. This joint is an improvement over the previous one presented by the same authors because it is more robust. The design iterations are presented and the final system has been modeled including some nonlinear blocks. A control architecture is proposed that allows compliant control to be used under adverse conditions or in uncontrolled environments. The presented joint is a cost-effective solution that can be used when normal rigid joints are not suitable.